The Creation of an Objective Assessment Tool for Ultrasound-Guided Regional Anesthesia Using the Delphi Method. Issue 3 (1st May 2012) - Cheung, Jeffrey J.H.; Chen, Ewen W.; Darani, Rosemin; McCartney, Colin J.L.; Dubrowski, Adam; Awad, Imad T.
Abstract : Background and Objectives: The assessment of technical skills in ultrasound-guided regional anesthesia is currently subjective and relies largely on observations of the trainer. The objective of this study was to develop a checklist to assess training progress and to detect training gaps in ultrasound-guided regional anesthesia using the Delphi method. Methods: A 30-item checklist was developed and then e-mailed to 18 reviewers for feedback. The checklist was modified on the basis of their feedback. This process of iteration was repeated until no further feedback was received, and a consensus was reached on the final composition of the checklist. A global rating scale (GRS) was introduced as a result of the feedback. Results: Three rounds of feedback were required to reach consensus on the composition of the checklist and the GRS. The final checklist contains 22 items, and the GRS contains 9 categories. Conclusions: Using the Delphi method, a checklist and GRS were developed. These tools can serve as an objective means of assessing progress in ultrasound technical skills acquisition.